2014
DOI: 10.1016/j.stemcr.2014.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Specific Cell-Surface Markers of Adipose-Derived Stem Cells from Subcutaneous and Visceral Fat Depots

Abstract: SummaryAdipose-derived stem/stromal cells (ASCs) from the anatomically distinct subcutaneous and visceral depots of white adipose tissue (WAT) differ in their inherent properties. However, little is known about the molecular identity and definitive markers of ASCs from these depots. In this study, ASCs from subcutaneous fat (SC-ASCs) and visceral fat (VS-ASCs) of omental region were isolated and studied. High-content image screening of over 240 cell-surface markers identified several potential depot-specific m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
125
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(134 citation statements)
references
References 21 publications
(22 reference statements)
8
125
0
Order By: Relevance
“…The selection of media modifies cell morphology, population doubling-time, membrane fragility, and the expression of certain surface markers accompanying multipotent phenotypes ex vivo. Table 2 indicates the list of markers we have scrutinized on PHADs by flow cytometry: 1) the membrane metallo-endopeptidase (CD10), previously identified as a potent mesenchymal like-cell concentrator on perivascular cells [46] and fat cells derived from lipoaspirates [47], 2) the hematopoietic progenitor cell antigen CD34, widely studied due to its therapeutic potential in vasculogenesis, osteogenesis [48], and chondrogenesis [49] with debatable hepatogenic and neurogenic potential by peripheral blood and bone marrow-derived CD34-positive cells [50,51], and 3) and the Neuron-Glial 2 antigen (NG2), initially described in pericytes promoting multilineage potential [52] demonstrating an augment from 7.2%->95% for CD10, <1%-40% for CD34, and 1.2%-6% for NG2 after one week of chemically defined and serum-free media transition. The mechanism by which this condition alters the cell's epigenetic regulation of the transcription of these markers is not yet known and will be later investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of media modifies cell morphology, population doubling-time, membrane fragility, and the expression of certain surface markers accompanying multipotent phenotypes ex vivo. Table 2 indicates the list of markers we have scrutinized on PHADs by flow cytometry: 1) the membrane metallo-endopeptidase (CD10), previously identified as a potent mesenchymal like-cell concentrator on perivascular cells [46] and fat cells derived from lipoaspirates [47], 2) the hematopoietic progenitor cell antigen CD34, widely studied due to its therapeutic potential in vasculogenesis, osteogenesis [48], and chondrogenesis [49] with debatable hepatogenic and neurogenic potential by peripheral blood and bone marrow-derived CD34-positive cells [50,51], and 3) and the Neuron-Glial 2 antigen (NG2), initially described in pericytes promoting multilineage potential [52] demonstrating an augment from 7.2%->95% for CD10, <1%-40% for CD34, and 1.2%-6% for NG2 after one week of chemically defined and serum-free media transition. The mechanism by which this condition alters the cell's epigenetic regulation of the transcription of these markers is not yet known and will be later investigated.…”
Section: Discussionmentioning
confidence: 99%
“…AD-MSCs are characterized by positive expression of CD9, CD13, CD29, CD44, CD49e, CD54, CD59, CD73, CD90, CD105, CD106, CD146, CD166, and STRO-1 and negative expression of hematopoietic markers, such as CD11b, CD14, CD19, CD31, CD34, CD45, CD56, CD133, CD144, CD146, and HLA-DR (Zuk et al 2002;Ong et al 2014;Li et al 2015) (Table 1).…”
Section: Adipose-derived Mscsmentioning
confidence: 99%
“…We suspect a different way of adipogenesis activation in those cell types. Recently, Ong et al (2014) reported that high expression of CD200 in ADSC obtained from visceral fat correlates with low adipogenic capacities in humans and mice. CD200, also called OX2, is a member of the immunoglobulin superfamily of proteins, and its expression is related to various immunoregulatory activities such as cancer growth, autoimmune and allergic disorders, infection, etc.…”
Section: First Induction Cycle Second Induction Cycle Third Inductionmentioning
confidence: 99%